Magnetically recyclable Fe3O4@SiO2/Bi2WO6/Bi2S3 with visible-light-driven photocatalytic oxidative desulfurization. (October 2019) - Guo, Li; Zhao, Qiang; Wang, Chan; Shen, Huidong; Han, Xuanxu an; Zhang, Kailai; Wang, Danjun; Fu, Feng
Graphical abstract: Magnetic Fe3 O4 @SiO2 /Bi2 WO6 /Bi2 S3 heterostructures was successfully prepared by the multistep process, which exhibits high stability an excellent photocatalytic activity for RhB decomposition and photocatalytic oxidation desulfurization. Highlights: Magnetic F-BWO-BS was obtained by the multistep process. Bi2 S3 QDs was deposited on the surface of Bi2 WO6 to obtain the magnetic F-BWO-BS heterostructures.via a precipitation-deposition method. The synthesized F-BWO-BS exhibits the enhanced photocatalytic activities for RhB decomposition and Photo-Cat-ODS. The possible mechanism of enhanced photocatalytic activity was proposed. Abstract: Novel core-shell structural magnetic Fe3O4@SiO2/Bi2WO6 (F-BWO) was obtained by a multistep process. Bi2S3 Quantum Dots (QDs) with the size of about 5 nm were deposited on the surface of Bi2WO6 "shell" to obtain Fe3O4@SiO2/Bi2WO6/Bi2S3 (F-BWO-BS) heterostructures. The experimental results indicated that F-BWO-BS exhibits the enhanced fuel oil photocatalytic-oxidative-desulfurization (Photo-Cat-ODS) and RhB photocatalytic degradation activity than that of F-BWO. The as-prepared F-BWO-BS-2 exhibited the best activity, the rate constant ( kapp /min −1 ) for RhB photocatalytic degradation is approximately 1.5 times higher than that of F-BWO. Furthermore, the F-BWO-BS-2 exhibited the best Photo-Cat-ODS activity, the desulfurization rate could reach 100% after illumination for 1.5 h. The enhanced photocatalytic activity of F-BWO-BS can be attributed to the synergistic effect of magnetic Fe3 O4 @SiO2 support − "core", Bi2 WO6 − "shell" and Bi2 S3 QDs. The experimental result also revealed that magnetic F-BWO-BS photocatalyst is easily magnetically separated with good stability and recyclability.